Interprofessional Education Learning Evaluation: Based on Core Competencies Interprofessional Education Collaborative - Haulaini, Shahiroh; Mita, Mita; Elvinda, Esty; Annafiatuzakiah, Annafiatuzakiah; Sinaga, Clara Ritawany (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2025)
Background: The Interprofessional Education (IPE) Collaboration emphasizes  4 core crucial for effective collaboration   in health services. The four core competencies included values and ethics, roles and responsibilities, communication, teams, and collaboration.Objectives: This study aimed to evaluate the results of IPE learning at Tanjungpura University based on IPEC core competencies.Methods: A cross-sectional design was adopted, and data were collected through an online survey. The respondents comprised undergraduate students at the Faculty of Medicine at Tanjungpura University who had participated in IPE and were willing to fill out the questionnaire. Data were analyzedwith Jamovi software version 2.6.19 for descriptive and statistical analysis. The study examined the correlation of age, gender, and study program with IPE Core Competency statement.Results: A total of 101 respondents completed the survey, consisting of 80.20% females and 19.80% males, with an average age of 21.2 years. These respondents were enrolled in study programs of Pharmacy (85.15%), Medicine (8.9%), and Nursing (5.94%). No significant correlations were found  between age and gender with understanding of IPE Core Competencies (p-value > 0.05). However a correlation was observed between study programs and understanding of IPE Core Competencies statement "I had the opportunity to learn what interprofessional relationships are like" (p value <0.05), linked to roles and responsibilitiesConclusion:  IPE participation helps students achieve the four Core Competencies. Understanding of thsese competencies was not influenced by age or gender, but was related to study program, particularly in the core competencies of roles and responsibilities.